Transcranial direct current stimulation in affecting neuropsychiatric symptoms of post-COVID syndrome: No change in microstates and functional connectivity - Nina Biačková; Olga Laskov; Andrea Adamová; Václava Piorecká; Jan Štrobl; Stanislav Jiříček; Jan Hubený; Vlastimil Koudelka; Anna Čechová; Natalie-Anna Böhmová; Monika Klírová (PLoS ONE, 2026)
Introduction Neuropsychiatric symptoms of post-covid syndrome (PCS) involve fatigue, brain fog, cognitive impairment, or symptoms of depression and anxiety. These symptoms are in other diagnoses associated with electroencephalography (EEG) changes in microstates and functional connectivity. Transcranial direct current stimulation (tDCS) is effective in alleviating certain abovementioned symptoms in other diagnoses. The main objective was to evaluate EEG changes in PCS patients after tDCS intervention. Methods A randomised control trial (registered in ISRCTN database, No.: ISRCTN10942585) with 35 participants (n = 33 received the intervention) involved 20 applications (over four weeks) of tDCS (anode over F3, cathode over F4, duration 30 min, intensity 2mA). Participants were divided into active (n = 16) and sham (n = 17) groups. Resting-state EEG was measured at baseline, after two weeks (T1), and after the intervention (four weeks, T2) as an exploratory endpoint. Microstates and functional connectivity between F3 and F4 were analysed; differences between active and sham groups in change from baseline to T1 and from baseline to T2 were evaluated. Results EEG measurements from 26 participants (n = 13 for active and n = 13 for sham group) were included into the statistical analysis. No significant results were found. No serious adverse events were noted. Conclusions We did not find a significant difference in selected EEG parameters between active and sham groups. The possible reasons include choice of tDCS parameters (electrode montage or stimulation duration), and EEG variables selected for evaluation (microstates and functional connectivity). These results are in line with the results of cognitive and clinical assessment. However, the EEG endpoints were exploratory and the study was primarily powered for clinical results, therefore small effects cannot be excluded due to limited statistical power.